Impacts of morphological change and sea-level rise on stratification in the Pearl River Estuary - Ma, Mengyao; Zhang, Wenyan; Chen, Wei; Deng, Junjie; Schrum, Corinna (Frontiers in Marine Science, 2023)
The Pearl River Delta (PRD), where several megacities are located, has undergone drastic morphological changes caused by anthropogenic impact during the past few decades. In its main estuary, the water area has been reduced by 21% whilst the average water depth has increased by 2.24 m from 1970s to 2010s. The mainly human-induced morphological change together with sea level rise has jointly led to a remarkable change in the water stratification. However, the spatial and temporal variability of stratification in the estuary and associated driving mechanisms remain less understood. In this study, stratification in the Pearl River Estuary (PRE) in response to morphological change and external forcing is investigated by 3-dimensional numerical modeling. Simulation results indicate that stratification in the PRE exhibits distinct spatial and temporal variabilities. At a tidal-to-monthly time scale, variation of stratification is mainly driven by advection and straining through tidal forcing. At a monthly-to-seasonal scale, monsoon-driven river runoff and associated plume and fronts dominate the variation of stratification. Human-induced morphological change leads to an enhancement of stratification by up to four times in the PRE. Compared to an overwhelming human impact in the past few decades, future sea level rise would further enhance stratification, but to a much lesser extent than past human impacts. In addition, stratification in different areas of the estuary also responds differently to the driving factors. The western shoal of the estuary is most sensitive to changes in morphology and sea level due to its shallowness, followed by the channels and other parts of the estuary, which are less sensitive.